1995
DOI: 10.1073/pnas.92.19.8788
|View full text |Cite
|
Sign up to set email alerts
|

Stress and antidepressants differentially regulate neurotrophin 3 mRNA expression in the locus coeruleus.

Abstract: The mechanisms by which stress and antidepressants exert opposite effects on the course of clinical depression are not known. However, potential candidates might include neurotrophic factors that regulate the development, plasticity, and survival of neurons. To explore this hypothesis, we examined the effects of stress and antidepressants on neurotrophin expression in the locus coeruleus (LC), which modulates many of the behavioral and physiological responses to stress and has been implicated in mood disorders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
38
1

Year Published

1997
1997
2009
2009

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(45 citation statements)
references
References 45 publications
6
38
1
Order By: Relevance
“…This is in contrast to previous studies in the rat localizing NT-3 mRNA to A6, 5,32 suggesting that related species may differ in regional patterns of neurotrophin gene expression. Because neurotrophins are subject to retrograde 33 and anterograde transport, 34,35 other NT-3 expressing neuronal populations in adult brain 27,36,37 may supply noradrenergic cells with targetderived NT-3.…”
Section: Noradrenergic Neurons Do Not Express Nt-3contrasting
confidence: 55%
“…This is in contrast to previous studies in the rat localizing NT-3 mRNA to A6, 5,32 suggesting that related species may differ in regional patterns of neurotrophin gene expression. Because neurotrophins are subject to retrograde 33 and anterograde transport, 34,35 other NT-3 expressing neuronal populations in adult brain 27,36,37 may supply noradrenergic cells with targetderived NT-3.…”
Section: Noradrenergic Neurons Do Not Express Nt-3contrasting
confidence: 55%
“…Data from a transgenic mouse model overexpressing the full-length isoform of NTRK3 supports this hypothesis [Dierssen, et al, 2006] as these mice present anxiety-like behaviour and show increased cellularity in the LC and other catecholaminergic nuclei. Neurotrophin-3 has trophic effects on LC neurons and mediates the effect of stress and of some antidepressants on LC function and plasticity [Smith, et al, 1995].…”
Section: Discussionmentioning
confidence: 99%
“…In our experiment, we found a twofold decrease of NT-3 mRNA levels in the hippocampus in animals treated chronically with paroxetine. NT-3 levels have been reported to be increased in the hippocampus and in the locus coeruleus by repeated severe stress and decreased by electroconvulsive seizures (ECS) or by long-term treatment with desipramine or imipramine, but not with fluoxetine or trazodone (Smith et al 1995;Smith 1996). Karege et al (2005) reported a significant decrease of BDNF and NT-3 protein levels in the hippocampus of drug-free suicide victims compared with non-suicide controls.…”
Section: Paroxetine-induced Effects On Neurotrophic Factorsmentioning
confidence: 99%